Neonatal Abstinence Syndrome in Rural Appalachia. Issue 3 (18th June 2021) - Cain, Shannon M; Conway, Anne; Combs-Orme, Terri; Bruck, Sarah L; Cook, E Kyle; Thomas, Elizabeth
: As the United States faces the repercussions of the current opioid epidemic, it is important for social workers to be able to identify risks for poor birth outcomes in infants with neonatal abstinence syndrome (NAS). Although some studies have identified single risk factors, no studies have tested associations between total amount of risk (that is, cumulative risk) and birth outcomes in infants with NAS. Authors examined 318 mothers who used opioids during pregnancy and their infants' birthweight, length, head circumference, and Apgar scores (which measure overall infant health after birth). All infants were admitted to a neonatal intensive care unit in Appalachia and were diagnosed with NAS. Authors found that high cumulative risk during pregnancy was associated with lower birthweight and Apgar scores one and five minutes after birth as well as shorter length and smaller head circumference at birth. Social workers are encouraged to assess for the quantity of prenatal adversity experienced by the mothers they serve and to consider multicomponent, comprehensive community-based interventions to reduce cumulative risk.